2013
DOI: 10.1080/00380768.2013.813382
|View full text |Cite
|
Sign up to set email alerts
|

Boron deprivation immediately causes cell death in growing roots ofArabidopsis thaliana(L.) Heynh.

Abstract: Boron (B) is essential for the correct formation of cell wall structure because it is a component of borate-ester cross-links in pectin. Previously, we showed that removal of B from the culture medium immediately induced stress responses in suspension-cultured tobacco (Nicotiana tabacum L.) cells, but the mechanism by which cells exhibit such rapid responses remained unclear. In this study, we characterized the early responses of Arabidopsis thaliana (L.) Heynh. to B deprivation. Deprivation of B for 1 h cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…The accumulation of reactive oxygen species (ROS) was observed in the areas stained with Evans blue, suggesting the involvement of ROS in rapid cell death. Similar rapid cell death and ROS accumulation in the root elongation zone were induced by Ca 2+ deprivation, another cross-linker of pectin, but not by magnesium or potassium deprivation (Oiwa et al 2013). This difference suggests that the rapid induction of cell death is not simply a response to essential nutrient deprivation, but associated specifically with the failure in pectin cross-linking.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The accumulation of reactive oxygen species (ROS) was observed in the areas stained with Evans blue, suggesting the involvement of ROS in rapid cell death. Similar rapid cell death and ROS accumulation in the root elongation zone were induced by Ca 2+ deprivation, another cross-linker of pectin, but not by magnesium or potassium deprivation (Oiwa et al 2013). This difference suggests that the rapid induction of cell death is not simply a response to essential nutrient deprivation, but associated specifically with the failure in pectin cross-linking.…”
Section: Introductionmentioning
confidence: 84%
“…We have previously reported that transferring the suspension-cultured tobacco cells to a B-free medium induces the activation of calcium ion (Ca 2+ ) channels within a few minutes and the expression of stress-responsive genes within 1 h or earlier (Kobayashi et al 2004;Koshiba et al 2010). Such a rapid response has been observed in the roots of intact plants as well (Oiwa et al 2013). Hydroponically cultured Arabidopsis plants exhibited the upregulation of stress-responsive genes within 1 h after transfer to a B-free medium.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why meristem-rich tissues that contain many cells undergoing division and expansion, such as immature tassels and ears, are more strongly affected than mature leaves. The defects in tls1 mutants seen later in development, such as altered cell shape and reduced cell integrity, as visible by histology, are also likely due to defects in the cell wall integrity (Fleischer et al, 1998;Ryden et al, 2003;Ahn et al, 2006;Koshiba et al, 2009;Reboul and Tenhaken, 2012;Oiwa et al, 2013). However, the fact that the leaves have defects despite having normal cross-linking of RG-II suggests that B is also involved in other processes occurring after organogenesis has occurred (Bassil et al, 2004).…”
Section: Cell Wall Integrity Is Critical For Meristem Functionmentioning
confidence: 92%
“…The production of reactive oxygen species and subsequent cell death has also been reported as an immediate downstream event of boron deprivation in cultured tobacco cells as well as in Arabidopsis roots. However, this appears to be a secondary effect associated with defective pectin cross-linking (Koshiba et al, 2009;Oiwa et al, 2013). We therefore propose that the lack of a proper cell wall structure caused by lower boron content results in cell expansion defects and eventually cell death in all inflorescence tissues, including meristems and floral organs.…”
Section: Boron Transport Is Required For the Structural Integrity Of mentioning
confidence: 97%